Synthesis and biological evaluation of peptide-derived TSLP inhibitors. Issue 20 (15th October 2017) - Park, Seonghu; Park, Yeeun; Son, Sang-Hyun; Lee, Kiho; Jung, Yong Woo; Lee, Ki Yong; Jeon, Young Ho; Byun, Youngjoo
Graphical abstract: Abstract: Thymic stromal lymphopoietin (TSLP) is a type II cytokine which is associated with most inflammatory allergic disorders in humans. It is produced mainly by epithelial cells with important role in the development of chronic inflammatory diseases by activating T-helper cell type-2 (TH 2) pathways. In this study, a total of 16 peptides were prepared by solid phase peptide synthesis based on amino acid sequences of the interface between TSLP and TSLP receptor. Their TSLP inhibition activities were determined by ELISA assay. Among them, three peptides (6 −8 ) exhibited >50% inhibition at concentration of 0.3 mM. They can be used as hit compounds for developing peptide-based TSLP inhibitors.